PENDIDIKAN PENGAWASAN PEMILU BAGI MASYARAKAT UNTUK MEWUJUDKAN PEMILU BERINTEGRITAS - Gokma Toni Parlindungan S; Michael Manarov Gultom (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2023)
Quality, transparent and fair elections are the main foundation for the continuation of a healthy democracy. To achieve this, education on election supervision for the public plays an important role in ensuring an election process with integrity and prioritizing the principles of fairness and integrity. This article reviews the importance of election supervision education and its implications in realizing the principles of fairness and integrity of elections. First, election supervision education provides an in-depth understanding of the public regarding the electoral process, including the rules that apply and their roles and responsibilities in the process. With a good understanding, the public can actively participate in monitoring and ensure that elections run according to democratic principles. Second, election supervision education equips the public with the necessary supervisory skills, such as monitoring campaign activities, voting and vote counting. These skills include understanding control protocols, using information technology, and reporting monitoring results. With these skills, the community can carry out supervision effectively and accurately. Furthermore, election supervision education also emphasizes the importance of supervisory ethics, including neutrality, honesty and professionalism in carrying out supervisory duties. The community is given an understanding of the importance of maintaining integrity and fairness in carrying out supervisory duties, so as to create an environment of supervision with integrity and trustworthiness. Finally, election supervision education encourages collaboration and monitoring networks between communities, civil society organizations, and related institutions. Through this collaboration, information exchange, coordination of monitoring activities, and mutual support in reporting and following up on election violations can be carried out more effectively. This article underscores the importance of education for election supervision for society in realizing the principles of fairness and integrity. With proper education, it is hoped that the community can play an active and responsible role in maintaining the integrity of elections, overseeing their implementation, and reporting and following up on violations that occur. Thus, elections that are democratic, fair and with integrity can be realized.Keywords: Supervision, Elections, Society.